The SPARC water vapour assessment II: Comparison of stratospheric and lower mesospheric water vapour time series observed from satellites - Khosrawi, Farahnaz; Lossow, Stefan; Stiller, Gabriele P.; Rosenlof, Karen H.; Urban, Joachim; Burrows, John P.; Damadeo, Robert P.; Eriksson, Patrick; García Comas, Maia; Gille, John C.; Kasai, Yasuko; Kiefer, Michael; et al. (Atmospheric Measurement Techniques, 2018)
Open access. © Author(s) 2018. This work is distributed under the Creative Commons Attribution 4.0 License. Time series of stratospheric and lower mesospheric water vapour using 33 data sets from 15 different satellite instruments were compared in the framework of the second SPARC (Stratosphere-troposphere Processes And their Role in Climate) water vapour assessment (WAVAS-II). This comparison aimed to provide a comprehensive overview of the typical uncertainties in the observational database that can be considered in the future in observational and modelling studies, e.g addressing stratospheric water vapour trends. The time series comparisons are presented for the three latitude bands, the Antarctic (80°-70°S), the tropics (15°S-15°N) and the Northern Hemisphere mid-latitudes (50°-60°N) at four different altitudes (0.1, 3, 10 and 80hPa) covering the stratosphere and lower mesosphere. The combined temporal coverage of observations from the 15 satellite instruments allowed the consideration of the time period 1986-2014. In addition to the qualitative comparison of the time series, the agreement of the data sets is assessed quantitatively in the form of the spread (i.e. the difference between the maximum and minimum volume mixing ratios among the data sets), the (Pearson) correlation coefficient and the drift (i.e. linear changes of the difference between time series over time). Generally, good agreement between the time series was found in the middle stratosphere while larger differences were found in the lower mesosphere and near the tropopause. Concerning the latitude bands, the largest differences were found in the Antarctic while the best agreement was found for the tropics. From our assessment we find that most data sets can be considered in future observational and modelling studies, e.g. addressing stratospheric and lower mesospheric water vapour variability and trends, if data set specific characteristics (e.g. drift) and restrictions (e.g. temporal and spatial coverage) are taken into account. © ...